Высокоэффективная газотурбинная установка для ГПА - Спицын, В. Е.; Боцула, А. Л.; Соломонюк, Д. Н.; Чобенко, В. Н. (НТУ "ХПИ", 2008)
Main features of a new high-performance 16 MW recuperative gas turbine for developing of new gascompressor units and for compressor stations modernization are presented.
Keywords: компрессоры; газотурбинный привод; экономичность; ремонт; регулируемый сопловый аппарат; ротор; газогенератор